HALAL TOURISM DEVELOPMENT STRATEGY AS A SUSTAINABLE ECONOMY DRIVER BASED ON MAQASHID SYARIAH - sumpena, mochamad (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
In the era of globalization and rapid growth of the tourism industry, a halal tourism development strategy has become an urgent need to encourage a sustainable economy based on the principles of Maqashid Sharia. This research aims to analyze halal tourism development strategies as a driving element for sustainable economic growth based on the concept of Maqashid Sharia. The research method used is a qualitative approach. The results of this research confirm that halal tourism has the potential to positively impact the economy sustainably. This approach involves key components such as halal food, accommodation that is friendly to Muslim needs, and interactions with religious norms. This creates an environment that is in line with Maqashid Sharia, which involves the protection of religion (Hifz al-Din), soul (Hifz al-Nafs), intellect (Hifz al-Aql), descendants (Hifz al-Nasl), property (Hifz al-Mal), and environment (Hifz al-Bi’ah).  In the context of the halal tourism development strategy, three important factors were identified: the development of infrastructure that supports halal principles, the promotion of appropriate destinations, and the implementation of the principles of crowdfunding within the Sharia framework.